1984
DOI: 10.2527/jas1984.5941026x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and Uterine Morphology and Function in Angus and Brahman Cows3

Abstract: Ovarian characteristics, daily serum progesterone (P4) and estradiol-17 beta (E2) concentrations (d 7 through 17) and uterine luminal secretory protein components and histological variables were evaluated in parous Bos taurus (Angus, n = 20) and Bos indicus (Brahman, n = 19) cows. Cows were slaughtered on d 17 (estrus = d 0) for measurement of ovarian structures, flushing of uteri and removal of uterine tissue for histological evaluation. Cows were placed into one of three reproductive categories: nonpregnant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
3
15

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 0 publications
4
32
3
15
Order By: Relevance
“…In studies with Nelore cattle, the diameter of ovulatory follicle was between 11 and 14 mm (Figueiredo et al, 1997;Sartorelli et al, 2005;Sartori et al, 2016), and the maximum diameter of the ovulatory follicle in Holstein cattle was between 13 and 19 mm (Ginther et al, 1989;Sartori et al, 2002aSartori et al, , 2004. Similarly, the CL diameter of B. indicus ranged from 17 to 21 mm or ~2.5 to 5.0 cm 3 (Segerson et al, 1984;Rhodes et al, 1995;Figueiredo et al, 1997;Bó et al, 2003;Sartori et al, 2016), whereas the CL diameter of B. taurus ranged from 20 and 30 mm or ~4.0 to 14.0 cm 3 (Ginther et al, 1989;Bó et al, 2003;Sartori et al, 2004Sartori et al, , 2016.…”
Section: Differences In Reproductive Physiology Between B Indicus Anmentioning
confidence: 98%
“…In studies with Nelore cattle, the diameter of ovulatory follicle was between 11 and 14 mm (Figueiredo et al, 1997;Sartorelli et al, 2005;Sartori et al, 2016), and the maximum diameter of the ovulatory follicle in Holstein cattle was between 13 and 19 mm (Ginther et al, 1989;Sartori et al, 2002aSartori et al, , 2004. Similarly, the CL diameter of B. indicus ranged from 17 to 21 mm or ~2.5 to 5.0 cm 3 (Segerson et al, 1984;Rhodes et al, 1995;Figueiredo et al, 1997;Bó et al, 2003;Sartori et al, 2016), whereas the CL diameter of B. taurus ranged from 20 and 30 mm or ~4.0 to 14.0 cm 3 (Ginther et al, 1989;Bó et al, 2003;Sartori et al, 2004Sartori et al, , 2016.…”
Section: Differences In Reproductive Physiology Between B Indicus Anmentioning
confidence: 98%
“…O peso do CL está relacionado com sua capacidade de produzir progesterona, hormônio intimamente relacionado com a manutenção de um ambiente útero-tubárico adequado ao desenvolvimento embrionário e manutenção do próprio CL durante o período crítico da vida embrionária (da ovulação à implantação), quando ocorre o reconhecimento materno da gestação (Fields & Fields, 1996). Fêmeas zebuínas apresentaram CL menor, com menor conteúdo de progesterona por grama de tecido luteal (Segerson et al, 1984). Neste aspecto, estudos anteriores reportaram que a detecção do CL por palpação transretal é mais difícil em zebuínos do que em taurinos (Plasse et al, 1968a;Vale Filho et al, 1986).…”
Section: Resultsunclassified
“…It goes without saying that follicle sizes could be categorized into 3 classes as depicted in Table 1. Several studies have also characterized follicular -wave dynamics in Bos indicus cattle and indicated that Bos indicus cattle have smaller diameters of the dominant follicles and corpus luteums (B.O et al, 2003) and lower serum progesterone concentrations (Segerson et al, 1984) relative to those of Bos Taurus Cattle. Previous studies also showed that the diameter of the dominant follicle at the time of deviation has been reported to be smaller in Nelore (6.0 to 6.3mm) Sartorelli et al, (2005) than in Holstein (8.5m) cattle (Ginther et al, 1996).…”
Section: IImentioning
confidence: 99%